Concomitant tacrolimus and ketorolac therapy in pediatric liver transplant recipients: Teaching old dogma new tricks. Issue 1 (19th November 2020) - Chen, Justin; Salerno, David; Breslin, Nadine; Chowdhury, Tasnim; Lobritto, Steven; Martinez, Mercedes; Goldner, Dana; Vittorio, Jennifer
Abstract: Nonsteroidal anti‐inflammatory drugs (NSAIDs), such as ketorolac, are effective analgesic medications, but concerns for nephrotoxicity have limited their role for pain control following pediatric liver transplantation (LT). Calcineurin inhibitors (CNIs) and NSAIDs share a similar mechanism of nephrotoxicity, and concomitant administration is traditionally discouraged. A retrospective review of pediatric LT recipients was conducted between 1/1/2015 and 12/31/2019 at a single center. Patients were stratified based on receipt of ketorolac. The primary outcome was the incidence of acute kidney injury (AKI). Secondary outcomes included serum creatinine, urine output, estimated glomerular filtration rate, bleeding incidence, oral morphine milligram equivalents, and hospital length of stay (LOS). The incidence of AKI was similar between the two groups with 25.8% of patients in the ketorolac group versus 29.2% of patients in the nonketorolac group ( p  = .475) meeting criteria in the first 10 days post‐transplant. Opioid requirements were less in the ketorolac group ( p  < .001), who also demonstrated shorter LOS compared with nonketorolac patients ( p  = .033). Concurrent CNI and ketorolac use did not result in an increased incidence of AKI in the early post‐LT period and resulted in significantly lower opioid requirements along with a decreased hospital LOS.